CLIMATE CHANGE AND ITS EFFECTS ON FUTURE GENERATIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a deep analysis of climate change and its long-term consequences on future generations, encompassing environmental, social, economic, and health aspects. As global temperatures continue to rise due to greenhouse gas emissions, the planet faces increased sea levels, extreme weather events, biodiversity loss, food insecurity, and economic disruption. The article explores how these environmental shifts will affect children born today, their livelihoods, mental and physical health, economic stability, and social structures. Drawing from scintific literature, climate reports, and international policies, the paper discusses potential mitigation strategies and the role of global cooperation in ensuring a livable future.